Type of financing dental care and frequency of dental visits among patients treated with implants - Szymańska, Jolanta; Koszuta, Agnieszka; Rosiak, Joanna (Polish Journal of Public Health, 2014)
Introduction. Many factors affect the oral health of the population. These include individual factors, the effectiveness of dental care, life styles and political, economic and environmental factors. Aim. The aim of the study was to evaluate the type of financing dental care and frequency of dental visits among patients treated with implants because of missing teeth. Material and methods. The survey was conducted among 464 patients of both genders aged 20-74 years, treated with dental implants at the Non-Public Healthcare Centre “Dental” in Tomaszów Mazowiecki. The patients answered questions included in anonymous questionnaire. The questions concerned age, education, type of dental care financing and frequency of dental visits. Results. Results of the survey indicate that among patients treated with implants there were over 14-times more people benefiting from dental care in private clinics providing preventive and restorative treatments at full cost, compared with people using dental services funded by the National Health Fund. Just over 16% of the surveyed patients frequently enough, i.e. at least once in 6 months reported to the dentist. The frequency of dental visits increased with the education level – people with vocational and secondary education most often visited a dentist irregularly, when necessary, while those with higher education – once a year. Patients below 60 years reported to the dentist 1-2 times a year, whereas older – irregularly, when necessary. Conclusion. In preparing the patient for the treatment of missing teeth with implants one should be aware of his need for paying special attention to oral health and regular, sufficiently frequent follow-up visits which has a substantial impact on the course and therapeutic success in the implant prosthetic treatment.